Infective agents and polymyalgia rheumatica: key discussion points emerging from a narrative review of published literature - Ciro Manzo; Marco Isetta; Alberto Castagna (Rheumatology)
Introduction The aetiology of polymyalgia rheumatica (PMR) is unknown. Recently, reports on cases of PMR following the coronavirus disease 2019 (COVID-19) have revived the role of infection as an aetiological or triggering factor. It is estimated that patients with PMR have manifestations of giant cell arteritis (GCA) in < 20% of cases. To date, little is known on the potential role of infectious agents in facilitating this association. Given this background, we performed a review of published literature. Our first aim was to review and discuss the relationship between PMR and infective agents. Secondly, we compared data of PMR-only patients with PMR and overlapping GCA to seek any commonalities or differences regarding the type of infectious agent in these two subgroups.